Pharmacological properties of cholinergic receptor and further evidences of direct action of soman on earthworm dorsal muscle (author's transl) - Zhou Jian-qun; Zhou Ting-chong (Acta Pharmacologica Sinica, 2016)
The pharmacological properties of the cholinergic receptor on the earthworm (Eisenia foetida) dorsal longitudinal muscle were studied and the non-cholinergic receptor effect of soman was confirmed. Pilocarpine 10-3 M, arecoline 10-2 M and oxotremorine 10-2 M did not, while nicotine 10-3 M did, induce contractions of the muscle. The contraction elicited by ACh10-5 M was not abolished by atropine 10-4 M nor by hexamethonium 10-4 M，but could be strongly inhibited by d-tubocurarine 2.75 x 10-5 M and blocked by cobratoxin 0.2 mg/ml. The hydrolytic products of soman, fluoride and pinacolyl methyphosphonate did not show any effect on the muscle preparation. On the preparation poisoned by cobratoxin, as ACh effect disappeared entirely, soman still caused a contraction of the muscle. The results indicate that the ChR on the earth-worm dorsal longitudinal muscle resembles the N-ChR in the neuromuscular junction of vertebrate animals. We surmise that the contraction of the muscle elicited by soman does not relate to the hydrolytic products of soman and that the “soman-receptor” does not relate to N-ChR.